Psikologi penagihan dadah: satu tinjauan literatur - Nazira Sadiron; Mohammad Rahim Kamaluddin; Wan Shahrazad Wan Sulaiman; Rozainee Khairudin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Drug addiction is a social disease that imposes a serious implication towards the nation’s de-velopment and security. Statistik Agensi Antidadah Kebangsaan in 2017 shows that there is an abrupt increase in drug addicts that is dominated by males aged from 20 to 40 years old. Various factors have been identified as contributing factors in drug addction.; and intrinsic factors, namely psychological factors often are assumed as the contributing factors that cause one to engage in drug addiction. Therefore, the current paper aims to present psychological factors that are related to drug addiction. In the context of psychology, there are four main psychological aspects: personality, emotional, cognition and behavioural that are explored in relation to drug addiction. Archival and metasynthesis methods were employed to collect re-sources. It was done through electronic and manual searches. The current paper is hoped to provide resources for experts and related agencies in drawing a psychological intervention that is suitable for the drug addicts as well as individuals who are at high risk to fall into drug addiction.